Competition and the State - Cheng, Thomas K.; Lianos, Ioannis; Sokol, D. Daniel (Global competition law and economics., 2014)
Competition and the State analyzes the role of the state across a number of dimensions as it relates to competition law and policy across a number of dimensions. This book re-conceptualizes the interaction between competition law and government activities in light of the profound transformation of the conception of state action in recent years by looking to the challenges of privatization, new public management, and public-private partnerships. It then asks whether there is a substantive legal framework that might be put in place to address competition issues as they relate to the.